Analysis of the Death-Leading Accident in Working with Boom Reclaimer Device using the Tripod beta and SCAT Combined Method in a Steel Company - Akbr REZAGHOLIAN; Nabiollah MANSOURI; Tooraj DANA (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The purpose of this study was to combine the two methods of Tripod beta and SCAT to analyze the accidents, explain their leading details, and track the roots of events at the depth of organizational layers. Methods: This analytical-descriptive study was carried out in one of the steel companies in Iran. To conduct the study, we analyzed one of the death- leading events using the combination of SCAT and Tripod methods. We investigated the relationship between variables and analyzed the intermediate and root causes of the event by Tripod beta method.  Moreover, we proposed some control measures in the SCAT cause and effect table. The information achieved from the questionnaire and effects of the accidents' causes were studied and rated using the chi-square test and Friedman test, respectively. Results: The most important direct cause of the accident was "removal of bucket wheel (in the Boom Claimer device) from the shaft". The most important intermediary cause of the event was "lack of an appropriate immune system at the time of balance weight release". The most important rudimentary cause of the event was "inappropriate location of the device cabin in the original design". Furthermore, the most important control measure was “using harvesting equipment with new design". Conclusion: According to the statistical tests, we found a systematic connection between root causes and intermediate causes of the incident. Moreover, we observed that the effect of root causes and intermediary causes were not similar regarding the accident.